2016
DOI: 10.1155/2016/9317194
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Observational Study of the Use of Saline Uterine Hydrosonography for the Diagnosis and Assessment of Uterine Cavity Lesions in Women

Abstract: Aim of this study was to evaluate the performance of saline hydrosonography (HSGM) (also known as saline infusion sonography (SIS)) against transvaginal ultrasound scan (TVS) and hysteroscopy in the diagnosis of uterine cavity lesions. Diagnostic hysteroscopy with biopsy is considered as the “gold standard” to diagnose intrauterine abnormalities. The introduction of HSGM has improved the diagnostic capability of ultrasound. It is important to establish the efficacy and safety of HSGM before it is widely recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Our sensitivity of 75%, specificity of 100%, positive predictive value of 75%, and negative predictive value of 72% for saline infusion sonohysterography in diagnosing endometrial polyps are similar to those reported by other authors [6,[14][15][16][17]. The procedure is also much better tolerated compared to hysteroscopy [15,16].…”
Section: Discussionsupporting
confidence: 88%
“…Our sensitivity of 75%, specificity of 100%, positive predictive value of 75%, and negative predictive value of 72% for saline infusion sonohysterography in diagnosing endometrial polyps are similar to those reported by other authors [6,[14][15][16][17]. The procedure is also much better tolerated compared to hysteroscopy [15,16].…”
Section: Discussionsupporting
confidence: 88%
“…Figure 2 shows the risk of bias and concerns regarding applicability in the included studies. For risk of bias and concerns regarding applicability, in the patient selection domain, one study 19 had an unclear risk of bias regarding patient inclusion criteria and five studies 21,23,29,32,35 were considered as having a high risk for bias since they excluded patients with ultrasonographic suspicion of endometrial cancer, uterine malformations, hormonal therapy, incomplete data or non-interpretable images.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…5,6 Saline-infused sonography can delineate submucosal fibroids from other intrauterine pathologies (such as endometrial polyps) and evaluate proximity of intramural fibroids from the endometrial cavity. 15,16 Three-dimensional (3D) ultrasonography allows for a clearer assessment of fibroid protrusion into the endometrial cavity as well as the thickness of the myometrium between the intramural portion of the mass and the serosa. 17 Lastly, magnetic resonance imaging (MRI) can be a useful tool in surgical planning to differentiate fibroids from adenomyomas, as well as reliably map out the number and size, vascularization patterns, and relationship of fibroids with the intrauterine cavity, serosal surface, and surrounding normal myometrium.…”
Section: Preoperative Evaluation and Imagingmentioning
confidence: 99%